Towards valid ‘serious non-fatal injury’ indicators for international comparisons based on probability of admission estimates - Cryer, C.; Miller, Ted; Lyons, R.; Macpherson, A.; Pérez, K.; Petridou, E.; Dessypris, N.; Davie, G.; Gulliver, P.; Lauritsen, J.; Boufous, S.; Lawrence, B.; et al. (BMJ Publishing Group, 2017)
© 2017, BMJ Publishing Group. All rights reserved.Background Governments wish to compare their performance in preventing serious injury. International comparisons based on hospital inpatient records are typically contaminated by variations in health services utilisation. To reduce these effects, a serious injury case definition has been proposed based on diagnoses with a high probability of inpatient admission (PrA). The aim of this paper was to identify diagnoses with estimated high PrA for selected developed countries. Methods The study population was injured persons of all ages who attended emergency department (ED) for their injury in regions of Canada, Denmark, Greece, Spain and the USA. International Classification of Diseases (ICD)-9 or ICD-10 4-digit/character injury diagnosis-specific ED attendance and inpatient admission counts were provided, based on a common protocol. Diagnosis-specific and region-specific PrAs with 95% CIs were calculated. Results The results confirmed that femoral fractures have high PrA across all countries studied. Strong evidence for high PrA also exists for fracture of base of skull with cerebral laceration and contusion; intracranial haemorrhage; open fracture of radius, ulna, tibia and fibula; pneumohaemothorax and injury to the liver and spleen. Slightly weaker evidence exists for cerebellar or brain stem laceration; closed fracture of the tibia and fibula; open and closed fracture of the ankle; haemothorax and injury to the heart and lung. Conclusions Using a large study size, we identified injury diagnoses with high estimated PrAs. These diagnoses can be used as the basis for more valid international comparisons of life-threatening injury, based on hospital discharge data, for countries with welldeveloped healthcare and data collection systems.